Drug-loaded ZIF8 surface modified polycaprolactone stent as well as preparation method and application thereof
By wrapping the adhesive layer and the drug-loaded layer on the polycaprolactone stent, ZIF8 deposition and drug encapsulation are promoted, and the problems of insufficient bone activity and sudden drug release in the prior art are solved, achieving efficient bone regeneration and antibacterial effects.
Patent Information
- Application Number
- CN202411925410.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-22
AI Technical Summary
The existing polycaprolactone-based stents are insufficient in promoting bone activity. The drug release of ZIF8-carried drugs is large and the preparation process is complex, making it difficult to industrialize.
By wrapping the adhesive layer and the drug-loaded layer on the surface of the polycaprolactone stent body in turn, ZIF8 is easier to deposit, imparting bioactivity to the stent, and encapsulating drugs inside ZIF8 to improve loading and controlled release effects.
It significantly induces osteogenesis and differentiation of stem cells, has antibacterial effects, reduces drug sudden release, and improves the bone activity and mechanical strength of the stent, which is suitable for the regeneration and repair of bone defects.
Smart Images

Figure CN119857180A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medical stents, and particularly relates to a drug-loaded ZIF8 surface-modified polycaprolactone stent and a preparation method and application thereof. Background Art
[0002] The ideal bone tissue engineering scaffold should have an interconnected porous network structure, providing interconnected channels for cell migration, ion transport, and cell-to-cell interaction. Conventional technologies include foaming, sacrificial template method, freeze drying and casting. 3D printing, also known as additive manufacturing technology, has penetrated into all walks of life due to its significant advantages in high precision, personalized manufacturing and complex shape construction. 3D printing obtains a three-dimensional entity by stacking raw materials layer by layer on a plane. Currently, the more mature 3D printing technologies include photopolymerization 3D printing, fused deposition 3D printing, inkjet 3D printing and laser sintering 3D printing. Among them, the basic principle of fused deposition 3D printing technology is that the base material is heated in the nozzle to a temperature slightly higher than its melting point. Under the action of pressure, the base material is extruded from the nozzle into filaments, and the nozzle moves in three dimensions under computer control, thereby stacking the base material filaments into shape. Compared with other scaffold preparation technologies, 3D printing technology can freely design the porosity and shape of the scaffold, which can well meet the needs of bone tissue engineering.
[0003] Polycaprolactone (PCL) is a commonly used material for 3D printing. It is widely used in the medical field because of its good biocompatibility, non-toxicity, degradability, and ability to induce tissue regeneration and provide a place for cell adhesion, proliferation and differentiation. However, the hydrophobicity of PCL will affect the adhesion of the scaffold, and its mechanical structure will be significantly damaged after degradation.
[0004] At present, there are many studies on polycaprolactone-based scaffolds, but the obtained polycaprolactone-based scaffolds or ZIF8 surface modified materials generally have the following problems: 1) The material has insufficient osteogenic activity; 2) ZIF8 carries drugs through electrostatic effects, and the drug release is large; 3) The preparation process is complicated and difficult to industrialize.
[0005] Therefore, it is of great significance to provide a scaffold with good osteogenic activity and low drug burst release. Summary of the invention
[0006] The present invention aims to solve one or more technical problems existing in the above-mentioned prior art and at least provide a beneficial choice. Specifically, the present invention provides a drug-loaded ZIF8 surface-modified polycaprolactone scaffold, which has good osteogenic activity and low drug burst release.
[0007] The inventive concept of the present invention: the polycaprolactone stent of the present invention comprises a polycaprolactone stent body, and an adhesive layer and a drug-loaded layer that sequentially wrap the polycaprolactone stent body; the drug-loaded layer comprises a drug and a zeolite imidazolate skeleton material; the drug is encapsulated in the zeolite imidazolate skeleton material (ZIF8). The surface of the polycaprolactone stent body of the present invention sequentially wraps the adhesive layer and the drug-loaded layer, so that ZIF8 is more easily deposited on the surface of the polycaprolactone stent body. Through the deposition modification of ZIF8, the polycaprolactone stent is endowed with biological activity, which can significantly induce osteogenic differentiation of stem cells and has antibacterial effects, making it more suitable for regeneration and repair of bone defects. In addition, the present invention encapsulates drugs inside ZIF8 instead of loading drugs through electrostatic adsorption, which greatly increases the loading amount of drugs, and is conducive to significantly enhancing the osteogenic activity of the stent and reducing drug burst release through controlled release of drugs.
[0008] Therefore, the first aspect of the present invention provides a drug-loaded ZIF8 surface-modified polycaprolactone stent.
[0009] Specifically, the drug-loaded ZIF8 surface-modified polycaprolactone stent includes a polycaprolactone stent body, and an adhesive layer and a drug-loaded layer that sequentially wrap the polycaprolactone stent body; the drug-loaded layer includes drugs and zeolite imidazolate skeleton material; and the drugs are encapsulated in the zeolite imidazolate skeleton material.
[0010] Specifically, ZIF8 is a porous crystalline material formed by the self-assembly of zinc ions and 2-methylimidazole. It has a large specific surface area, high porosity, convenient synthesis, and controllable size, and has outstanding advantages in the encapsulation and transportation of functional substances. At the same time, this type of material has excellent biocompatibility, its structure has good stability under physiological conditions, and ZIF8 hydrolysis will produce zinc ions with osteogenic activity, which has great application potential in biomedicine.
[0011] Preferably, the polycaprolactone stent body is a 3D printed stent.
[0012] Preferably, the component of the adhesive layer includes polyvinyl pyrrolidone.
[0013] Preferably, the matrix material of the polycaprolactone stent body includes polycaprolactone, and the molecular weight of the polycaprolactone is 27,000-65,000 Daltons; further preferably, the molecular weight of the polycaprolactone is 30,000-60,000 Daltons.
[0014] Preferably, the drug includes at least one of bone morphogenetic protein-2, bone morphogenetic protein-7, vascular endothelial cell factor, platelet-derived factor, curcumin, melatonin, alendronate sodium, naringin, resveratrol, dexamethasone, and gentamicin sulfate.
[0015] The second aspect of the present invention provides a method for preparing the drug-loaded ZIF8 surface-modified polycaprolactone scaffold described in the first aspect of the present invention.
[0016] Specifically, the method for preparing the drug-loaded ZIF8 surface-modified polycaprolactone stent comprises the following steps:
[0017] The polycaprolactone stent body is placed in a solution containing a binder, stirred, and reacted; the product after the reaction is mixed with a drug and a 2-methylimidazole aqueous solution, and then a zinc nitrate aqueous solution is added and reacted to obtain the drug-loaded ZIF8 surface-modified polycaprolactone stent.
[0018] Preferably, the method for preparing the drug-loaded ZIF8 surface-modified polycaprolactone scaffold comprises the following steps:
[0019] (1) placing the polycaprolactone stent body in a solution containing a binder, stirring and reacting, and obtaining a polycaprolactone stent wrapped with an adhesive layer;
[0020] (2) Mixing the drug, the polycaprolactone stent wrapped with the adhesive layer obtained in step (1) and an aqueous solution of 2-methylimidazole, then dripping an aqueous solution of zinc nitrate to react and obtain the polycaprolactone stent with the drug-loaded ZIF8 surface modified thereon.
[0021] Preferably, the molecular weight of the binder is 10000-58000 Dalton (Da); further preferably, the molecular weight of the binder is 9000-60000 Da.
[0022] Preferably, the binder comprises polyvinyl pyrrolidone.
[0023] Preferably, the solution is an ethanol-water solution, the mass volume ratio of the binder to the ethanol-water solution is (0.55-1.65) g:10 mL, and the volume fraction of ethanol in the ethanol-water solution is 45-85%; further preferably, the mass volume ratio of the binder to the ethanol-water solution is (0.6-1.5) g:10 mL, and the volume fraction of ethanol in the ethanol-water solution is 50-80%.
[0024] Preferably, the mass volume ratio of the polycaprolactone stent body and the ethanol aqueous solution containing the binder is (1.8-11) mg:1 mL; further preferably, the mass volume ratio of the polycaprolactone stent body and the ethanol aqueous solution containing the binder is (2-10) mg:1 mL.
[0025] Preferably, the stirring speed is 180-550 rpm, and the stirring time is 0.9-4.5 h; further preferably, the stirring speed is 200-500 rpm, and the stirring time is 1-4 h.
[0026] Preferably, in step (1), the reaction further includes a washing process.
[0027] Preferably, ethanol washing is used to remove excess binder.
[0028] Preferably, the concentration of 2-methylimidazole in the 2-methylimidazole aqueous solution is 22-65 mg / mL; further preferably, the concentration of 2-methylimidazole in the 2-methylimidazole aqueous solution is 25-60 mg / mL.
[0029] Preferably, the concentration of the drug in the 2-methylimidazole aqueous solution is 18-11000 μg / mL; further preferably, the concentration of the drug in the 2-methylimidazole aqueous solution is 20-10000 μg / mL.
[0030] Preferably, the concentration of zinc nitrate in the aqueous zinc nitrate solution is 2.7-20 mg / mL; further preferably, the concentration of zinc nitrate in the aqueous zinc nitrate solution is 3-18 mg / mL.
[0031] Preferably, the volume ratio of the 2-methylimidazole aqueous solution to the zinc nitrate aqueous solution is (2.7-10):1; further preferably, the volume ratio of the 2-methylimidazole aqueous solution to the zinc nitrate aqueous solution is (3-9):1.
[0032] Specifically, the present invention encapsulates the drug internally by encapsulating the drug in the preparation process of ZIF8, which requires controlling the formula. If the dosage relationship is not reasonably limited, the drug encapsulation cannot be well achieved. The present invention can achieve the purpose of effectively loading the drug by reasonably limiting the dosage relationship of the drug, zinc nitrate, and 2-methylimidazole.
[0033] Preferably, in step (2), the reaction further includes a washing and drying process.
[0034] Preferably, the method for preparing the polycaprolactone stent body comprises the following steps:
[0035] Put polycaprolactone into a printing barrel, match a needle, and print to obtain the polycaprolactone stent body.
[0036] Further preferably, the method for preparing the polycaprolactone stent body comprises the following steps:
[0037] Put the polycaprolactone film into the printing barrel, match the needle, set the printing parameters and heating temperature, and print layer by layer to obtain the polycaprolactone stent body.
[0038] Preferably, the needle diameter is 0.18-0.55 mm; further preferably, the needle diameter is 0.2-0.5 mm.
[0039] Preferably, the temperature of the barrel is 55-100°C; more preferably, the temperature of the barrel is 60-95°C.
[0040] Preferably, the temperature of the needle is 50-95°C; further preferably, the temperature of the needle is 55-90°C.
[0041] Preferably, the fiber spacing of the polycaprolactone fibers in the polycaprolactone stent body is (0.70-0.90) mm×(0.70-0.90) mm; further preferably, the fiber spacing of the polycaprolactone fibers in the polycaprolactone stent body is (0.75-0.85) mm×(0.75-0.85) mm; further preferably, the fiber spacing of the polycaprolactone fibers in the polycaprolactone stent body is 0.8 mm×0.8 mm.
[0042] Preferably, the fiber orientation of the polycaprolactone fibers in the polycaprolactone stent body is 0-90°.
[0043] Preferably, the printing speed is 7.5-18 mm / s; further preferably, the printing speed is 8-16 mm / s.
[0044] Preferably, the air pressure during printing is 300-420 kPa; further preferably, the air pressure during printing is 340-380 kPa.
[0045] Preferably, the support layer height during printing is 70-95% of the needle diameter; further preferably, the support layer height during printing is 75-95% of the needle diameter.
[0046] The third aspect of the present invention provides a use of the polycaprolactone scaffold described in the first aspect of the present invention in preparing a product for repairing and regenerating bone tissue defects.
[0047] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0048] (1) The surface of the polycaprolactone stent body of the present invention is sequentially coated with an adhesive layer and a drug-loaded layer, so that ZIF8 is more easily deposited on the surface of the polycaprolactone stent body. The polycaprolactone stent is endowed with biological activity through ZIF8 deposition modification, and can significantly induce osteogenic differentiation of stem cells, and has an antibacterial effect, making it more suitable for regeneration and repair of bone defects. In addition, the present invention encapsulates drugs inside ZIF8 instead of loading drugs through electrostatic adsorption, which greatly increases the loading amount of drugs, is conducive to significantly enhancing the osteogenic activity of the stent and reducing the sudden release of drugs through sustained and controlled release of drugs, and has good mechanical strength and biocompatibility, which can well meet the repair and regeneration of bone tissue defects.
[0049] (2) The preparation method of the present invention has a simple process, low requirements on equipment, and the raw materials are readily available from industrial sources, low cost, and easy to realize industrialization. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 This is a tensile strength diagram of polycaprolactone stents of Examples 1-4 and Comparative Examples 1-4 of the present invention;
[0051] Figure 2 The in vitro drug release performance curves of the polycaprolactone stents of Examples 1-4, Comparative Example 2 and Comparative Example 4 of the present invention;
[0052] Figure 3 This is the alkaline phosphatase activity diagram of the polycaprolactone scaffolds of Examples 1-4 and Comparative Examples 1-4 of the present invention. DETAILED DESCRIPTION
[0053] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.
[0054] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0055] Example 1
[0056] A method for preparing a drug-loaded ZIF8 surface-modified polycaprolactone stent comprises the following steps:
[0057] (1) 10 g of polycaprolactone (molecular weight of 40,000 Daltons) was placed in a printing barrel, the needle diameter was 0.25 mm, the barrel temperature was 60° C., the needle temperature was 65° C., the fiber spacing was 0.8 mm×0.8 mm, the printing rate was 8 mm / s, the fiber orientation was “0-90°”, the air pressure was 380 kPa, and the scaffold layer height was 75% of the needle diameter, and the polycaprolactone scaffold body was printed layer by layer;
[0058] (2) 20 mg of the polycaprolactone stent obtained in step (1) was immersed in 5 mL of an ethanol aqueous solution containing 0.375 g / mL polyvinyl pyrrolidone (Mw=29000) (the volume proportion of ethanol in the ethanol aqueous solution was 75%), and the mixture was mechanically stirred at a speed of 500 rpm for 2 h, and then washed with ethanol to remove excess polyvinyl pyrrolidone to obtain a polycaprolactone stent wrapped with polyvinyl pyrrolidone;
[0059] (3) 5 mg of curcumin and the polyvinyl pyrrolidone-coated polycaprolactone scaffold obtained in step (2) were placed in 90 mL of a 35 mg / mL 2-methylimidazole aqueous solution, and 15 mL of a 10 mg / mL zinc nitrate aqueous solution was added dropwise during stirring. After the reaction, the mixture was washed and dried to obtain a drug-loaded ZIF8 surface-modified polycaprolactone scaffold.
[0060] Example 2
[0061] (1) 10 g of polycaprolactone (molecular weight of 30,000 Daltons) was placed in a printing barrel, the needle diameter was 0.2 mm, the barrel temperature was 75°C, the needle temperature was 70°C, the fiber spacing was 0.8 mm×0.8 mm, the printing rate was 10 mm / s, the fiber orientation was "0-90°", the air pressure was 360 kPa, and the scaffold layer height was 95% of the needle diameter, and the polycaprolactone scaffold body was printed layer by layer to obtain the polycaprolactone scaffold body;
[0062] (2) 20 mg of the polycaprolactone stent obtained in step (1) was immersed in 2 mL of ethanol aqueous solution containing 0.3 g / mL polyvinyl pyrrolidone (Mw=30000) (the volume proportion of ethanol in the ethanol aqueous solution was 60%), and the mixture was stirred with magnetic force at a speed of 200 rpm for 4 h, and then washed with ethanol to remove excess polyvinyl pyrrolidone to obtain a polycaprolactone stent wrapped with polyvinyl pyrrolidone;
[0063] (3) 10 mg of alendronate sodium and the polyvinyl pyrrolidone-coated polycaprolactone stent obtained in step (2) were placed in 90 mL of a 60 mg / mL 2-methylimidazole aqueous solution, and 30 mL of a 9 mg / mL zinc nitrate aqueous solution was added dropwise during stirring. After the reaction, the mixture was washed and dried to obtain a drug-loaded ZIF8 surface-modified polycaprolactone stent.
[0064] Example 3
[0065] (1) 10 g of polycaprolactone (molecular weight 60,000 Daltons) was placed in a printing barrel, the needle diameter was 0.5 mm, the barrel temperature was 95°C, the needle temperature was 55°C, the fiber spacing was 0.8 mm×0.8 mm, the printing rate was 16 mm / s, the fiber orientation was "0-90°", the air pressure was 360 kPa, and the support layer height was 75% of the needle diameter. The polycaprolactone support body was obtained by printing layer by layer.
[0066] (2) 20 mg of the polycaprolactone stent obtained in step (1) was immersed in 10 mL of 0.6 g / mL polyvinyl pyrrolidone (Mw=10000) in an ethanol aqueous solution (the volume proportion of ethanol in the ethanol aqueous solution was 50%), and the mixture was stirred with a magnetic stirrer at a speed of 400 rpm for 1 h, and then washed with ethanol to remove excess polyvinyl pyrrolidone to obtain a polycaprolactone stent wrapped with polyvinyl pyrrolidone;
[0067] (3) 20 μg of bone morphogenetic protein 2 and the polyvinyl pyrrolidone-coated polycaprolactone scaffold obtained in step (2) were placed in 90 mL of a 25 mg / mL 2-methylimidazole aqueous solution, and 45 mL of a 3 mg / mL zinc nitrate aqueous solution was added dropwise during stirring. After the reaction, the solution was washed and dried to obtain a polycaprolactone scaffold with a drug-loaded ZIF8 surface modified thereon.
[0068] Example 4
[0069] (1) 10 g of polycaprolactone (molecular weight of 50,000 Daltons) was placed in a printing barrel, the needle diameter was 0.35 mm, the barrel temperature was 70°C, the needle temperature was 75°C, the fiber spacing was 0.8 mm×0.8 mm, the printing rate was 12 mm / s, the fiber orientation was "0-90°", the air pressure was 340 kPa, and the scaffold layer height was 80% of the needle diameter, and the polycaprolactone scaffold body was printed layer by layer;
[0070] (2) 20 mg of the polycaprolactone stent obtained in step (1) was immersed in 80% ethanol aqueous solution containing 8 mL of 0.64 g / mL polyvinyl pyrrolidone (Mw=58000), and the mixture was stirred at 300 rpm for 2 h, and then washed with ethanol to remove excess polyvinyl pyrrolidone to obtain a polycaprolactone stent coated with polyvinyl pyrrolidone;
[0071] (3) 3 mg of dexamethasone and the polyvinyl pyrrolidone-coated polycaprolactone stent obtained in step (2) were placed in 90 mL of a 40 mg / mL 2-methylimidazole aqueous solution, and 10 mL of an 18 mg / mL zinc nitrate aqueous solution was added dropwise during stirring. After the reaction, the solution was washed and dried to obtain a drug-loaded ZIF8 surface-modified polycaprolactone stent.
[0072] Comparative Example 1
[0073] The only difference between Comparative Example 1 and Example 1 is that the ZIF8 in Comparative Example 1 is not loaded with drugs, that is, in step (3) of Comparative Example 1, the drugs are not added to the 2-methylimidazole aqueous solution, and the rest is the same as Example 1.
[0074] The step (3) of Comparative Example 1 is specifically as follows:
[0075] The polyvinyl pyrrolidone-coated polycaprolactone stent obtained in step (2) was placed in 90 mL of a 35 mg / mL 2-methylimidazole aqueous solution, and 15 mL of a 10 mg / mL zinc nitrate aqueous solution was added dropwise during stirring. After the reaction, the mixture was washed and dried to obtain a polycaprolactone stent.
[0076] Comparative Example 2
[0077] The only difference between Comparative Example 2 and Example 1 is that Comparative Example 2 does not contain ZIF8, that is, in step (3) of Comparative Example 2, the drug and the polyvinyl pyrrolidone-coated polycaprolactone stent are not added to the 2-methylimidazole aqueous solution, and the zinc nitrate aqueous solution is not added dropwise. Instead, the drug and the polyvinyl pyrrolidone-coated polycaprolactone stent are added to 105 mL of the aqueous solution, and the rest is the same as Example 1.
[0078] The step (3) of Comparative Example 2 is specifically as follows:
[0079] 5 mg of curcumin and the polyvinyl pyrrolidone-coated polycaprolactone scaffold obtained in step (2) were placed in 105 mL of aqueous solution, stirred, washed, and dried to obtain a polycaprolactone scaffold.
[0080] Comparative Example 3
[0081] The only difference between Comparative Example 3 and Example 1 is that Comparative Example 3 does not contain ZIF8 and is not loaded with drugs, that is, in step (3) of Comparative Example 3, the drug is not added to the 2-methylimidazole aqueous solution, and the zinc nitrate aqueous solution is not added dropwise. Instead, the polyvinyl pyrrolidone-coated polycaprolactone stent obtained in step (2) is placed in 105 mL of aqueous solution, and the rest is the same as Example 1.
[0082] The step (3) of Comparative Example 3 is specifically:
[0083] The polyvinyl pyrrolidone-coated polycaprolactone scaffold obtained in step (2) was added into 105 mL of aqueous solution, stirred, washed and dried to obtain a polycaprolactone scaffold.
[0084] Comparative Example 4
[0085] The only difference between Comparative Example 4 and Example 1 is that Comparative Example 4 does not use polyvinyl pyrrolidone, that is, in step (2) of Comparative Example 1, the polycaprolactone stent body is not immersed in an ethanol aqueous solution containing polyvinyl pyrrolidone, and the rest is the same as Example 1.
[0086] Performance Testing
[0087] 1. Tensile strength test
[0088] After drying, the polycaprolactone stents of Examples 1-4 and Comparative Examples 1-4 were placed in an INSTON test machine (34sc -5 ) with a compression speed of 1 mm / min, and mechanical properties tests were performed. The tensile strength test results are shown in Figure 1 As shown. Figure 1 It can be seen that the tensile strength of the polycaprolactone scaffold without ZIF8 in Comparative Example 2-3 is lower than that in Example 1. Since no polyvinyl pyrrolidone is used in Comparative Example 4, less ZIF8 is deposited than in Example 1, and the mechanical properties are reduced.
[0089] 2. In vitro cytotoxicity evaluation
[0090] L929 mouse fibroblasts that had been cultured for 24 hours and were growing vigorously were digested and prepared into a density of 1.0×10 5 / mL, inoculated in a 96-well plate, 100μL per well; after the cells grow into a monolayer, remove the original culture medium, add 100μL of the test sample extract, blank control solution, positive control solution and negative control solution, respectively, with 6 replicates in each group, wherein the blank control solution is a complete culture medium containing 3g / L phenol; the positive control solution is an extract containing 0.3g / mL of high-density polyethylene in a complete culture medium after culturing at 37±1℃ for 24h. After the sample addition was completed, the 96-well plate was placed in a 37°C, 5% CO2 incubator for 24 hours; after 24 hours of culture, the original culture medium was aspirated, 50 μL MTT (1 mg / mL) was added to each well, and the culture was continued for 2 hours. After the end, the supernatant was aspirated, and 100 μL of 99.5% pure isopropanol was added to dissolve the crystals; the absorbance value was measured on an ELISA instrument with 570 nm as the main absorption wavelength and 650 nm as the reference wavelength to calculate the cell survival rate.
[0091] The cell viability was calculated according to the following formula: Cell viability (%) = 100 × OD 570e / OD 570b ;
[0092] OD 570e It is the average optical density of the test sample or control sample extract;
[0093] OD 570b is the average optical density of the blank.
[0094] The in vitro cell survival rates of the polycaprolactone scaffolds of Examples 1-4 and Comparative Examples 1-4 are shown in Table 1.
[0095] Table 1: In vitro cell survival rates of polycaprolactone scaffolds of Examples 1-4 and Comparative Examples 1-4
[0096]
[0097] It can be seen from Table 1 that the polycaprolactone scaffold prepared in the present invention has no cytotoxicity.
[0098] 3. Hemolytic performance test
[0099] According to the amount of blood used in the test, blood is collected from the heart of a healthy rabbit, such as 10 mL of blood, and 0.5 mL of potassium oxalate solution with a mass concentration of 20 g / L is added to prepare fresh anticoagulated rabbit blood; 8 mL of fresh anticoagulated rabbit blood is taken and diluted with 10 mL of sodium chloride injection with a mass concentration of 9 g / L. The test sample group (Example 1-4, Comparative Example 1-4) adds the test sample according to the extraction ratio (0.2 g / mL), and then adds 10 mL of sodium chloride injection; 10 mL of sodium chloride injection is added to each tube of the negative control group; 10 mL of distilled water is added to each tube of the positive control group. Three tubes are operated in parallel in each group. After all the test tubes are placed in a constant temperature water bath at (37 ± 1) ° C for 30 minutes, 0.2 mL of diluted rabbit blood is added to each test tube, gently mixed, and placed in a (37 ± 1) ° C water bath for 60 minutes. Pour out the liquid in the tube and centrifuge at 800g for 5 minutes, aspirate the supernatant and transfer it to a cuvette, and measure the absorbance at a wavelength of 545nm using a spectrophotometer. The absorbance of the test group and the control group is the average of the three tubes. The absorbance of the negative control tube should not be greater than 0.03; the absorbance of the positive control tube should be 0.8±0.3, otherwise the test should be repeated.
[0100] The hemolysis rate was calculated as follows:
[0101] Hemolysis rate (%) = (absorbance of the test sample group - absorbance of the negative control group) / (absorbance of the positive control group - absorbance of the negative control group) × 100%.
[0102] The hemolysis rate results of the polycaprolactone stents of Examples 1-4 and Comparative Examples 1-4 are shown in Table 2.
[0103] Table 2: Hemolysis rate of polycaprolactone stents in Examples 1-4 and Comparative Examples 1-4
[0104]
[0105] It can be seen from Table 2 that the hemolysis rate of the polycaprolactone stent prepared by the present invention is less than 5%, and there is no hemolysis risk.
[0106] 4. In vitro drug release performance test
[0107] The in vitro drug release performance evaluation method is as follows: at 37°C and 60rpm, 500mg of the polycaprolactone scaffolds of Examples 1-4, Comparative Example 2, and Comparative Example 4 were immersed in 200mL PBS (pH=7.4) in a constant temperature shaker, the test liquid was collected regularly, and an equal amount of PBS was supplemented. The collected test liquid was determined by high performance liquid chromatography (HPLC) for drug content, and compared with the total drug load in the product, the cumulative release rate of the drug was calculated.
[0108] The in vitro drug release performance curves of the polycaprolactone stents of Examples 1-4, Comparative Example 2, and Comparative Example 4 are shown in FIG. Figure 2 shown.
[0109] Depend on Figure 2 It can be seen that the release period of various drugs prepared in Examples 1-4 for the stents is more than 3 weeks. Comparative Example 2 does not contain ZIF8, and the drug curcumin is directly adsorbed on the surface of the stent, so that the burst release of the drug in the stent of Comparative Example 2 is significantly increased, and the release is basically completed in 1 week, that is, the release performance of Comparative Example 2 is significantly lower than that of Example 1; the drug-loaded ZIF8 in Comparative Example 4 is lower than that in Example 1, but the effect on the drug release curve is not obvious.
[0110] 5. In vitro osteogenic differentiation test of pre-osteoblasts
[0111] The polycaprolactone scaffolds prepared in Examples 1-4 and Comparative Examples 1-4 were irradiated and sterilized, immersed in DMEM basal culture medium at a concentration of 10 mg / mL, and extracted at 120 rpm in a 37°C shaker for 24 h. After the extraction, the mixture of the polycaprolactone scaffold and the culture medium was centrifuged at 1000 rpm, and the supernatant was collected, which was the extract. The collected extracts were diluted 2 times with the corresponding DMEM culture medium, and finally 10% fetal bovine serum was added to obtain a conditioned medium.
[0112] Mouse embryonic osteoblast precursor cells (MC3T3-E1 cells) were cultured at 1×10 5 The cells were inoculated in a 24-well plate at a density of 100 cells / mL. After 24 hours of adherent culture, the conditioned medium was replaced and cultured in an incubator at 37°C and 5% carbon dioxide atmosphere. The culture medium was replaced every 2-3 days. After 7 days of culture, the osteogenic differentiation performance of MC3T3-E1 cells was detected by the alkaline phosphatase secreted by them and measured by the pNPP method. The specific steps are as follows: MC3T3-E1 cells were washed with PBS solution and immersed in a PBS solution containing 0.1 mol / L glycine, 1 mmol / L magnesium chloride and 0.05% Triton X-100 (octoxynol); after the cells were dissolved, the dissolved solution was evenly mixed with disodium p-nitrophenyl phosphate, and the mixed solution was placed at 37°C for 30 minutes; then, the mixed solution was added dropwise to a 96-well plate, and the absorbance value of each well at a wavelength of 405 nm was measured by an ELISA reader.
[0113] Definition of alkaline phosphatase activity unit: In diethanolamine (DEA) buffer at pH 9.8, at 37°C, the amount of alkaline phosphatase required to hydrolyze para-nitrophenyl phosphate chromogenic substrate to produce 1 micromole of p-nitrophenol per minute is defined as one enzyme activity unit, also known as one DEA enzyme activity unit. In glycine buffer at pH 9.6, at 25°C, the amount of alkaline phosphatase required to hydrolyze para-nitrophenyl phosphate chromogenic substrate to produce 1 micromole of p-nitrophenol per minute is defined as one enzyme activity unit, also known as one glycine enzyme activity unit. One glycine enzyme activity unit is approximately equivalent to 3 DEA enzyme activity units. Based on the definition of enzyme activity, the alkaline phosphatase activity in the sample is calculated. The alkaline phosphatase activity of the polycaprolactone scaffolds of Examples 1-4 and Comparative Examples 1-4 are shown in the figure. Figure 3 shown.
[0114] Depend on Figure 3 It can be seen that the polycaprolactone scaffolds of Examples 1-4 of the present invention have a good effect of inducing cells to secrete alkaline phosphatase. In the case of no drug loading, the osteogenic activity of Comparative Example 1 is significantly reduced. Comparative Example 3 contains neither a ZIF8 layer with good biological activity nor a drug, and its alkaline phosphatase activity is the lowest. Comparative Example 2 does not contain a ZIF8 layer with good biological activity, and its alkaline phosphatase activity is between Comparative Examples 1 and 3. Comparative Example 4 does not contain polyvinyl pyrrolidone, which reduces the deposition of ZIF8, resulting in its alkaline phosphatase activity being lower than that of Example 1.
[0115] 6. Antibacterial performance test
[0116] Take fresh slant cultures of Staphylococcus aureus and Escherichia coli, count the live bacteria in the bacterial suspension, and prepare a 5×10-60 suspension with 0.03 mol / L PBS (pH=7.2-7.4) containing 1% peptone. 5 -10×10 6 cfu / mL of bacterial suspension. Place the polycaprolactone stent samples of Examples 1-4 and Comparative Examples 1-4 in sterile dishes, add 50 μL of bacterial suspension on each sample, record the time of adding bacteria to each tube, inoculate the blood plate 60 minutes after adding bacteria, and place the sample in a 5 mL nutrient broth tube. Culture the blood plates and broth tubes inoculated with bacteria at 37°C for 48 hours, observe the preliminary results, and continue to culture in sterile growth tubes until the 28th day. If the broth tube is turbid and there is bacterial growth on the blood plate, it is recorded as positive, indicated by (+); if it is still clear on the 35th day, it is considered as sterile growth, indicated by (–).
[0117] The antibacterial performance test results of the polycaprolactone stents of Examples 1-4 and Comparative Examples 1-4 are shown in Table 3.
[0118] Table 3: Test results of antibacterial properties of polycaprolactone stents in Examples 1-4 and Comparative Examples 1-4
[0119]
[0120] It can be seen from Table 3 that the polycaprolactone stents prepared in Examples 1-4 of the present invention all have good long-term antibacterial effects and can grow aseptically for 35 days. Comparative Examples 2 and 3 do not contain ZIF8 and have no antibacterial effects.
[0121] In summary, the surface of the polycaprolactone stent body of the present invention is sequentially wrapped with an adhesive layer and a drug-loaded layer, so that ZIF8 is more easily deposited on the surface of the polycaprolactone stent body, and the polycaprolactone stent is modified by ZIF8 deposition, and the bioactivity of the polycaprolactone stent is given, which can significantly induce osteogenic differentiation of stem cells, and has an antibacterial effect, making it more suitable for regeneration and repair of bone defects. In addition, the present invention encapsulates drugs inside ZIF8, rather than loading drugs by electrostatic adsorption, greatly improving the loading amount of drugs, which is conducive to significantly enhancing the osteogenic activity of the stent and reducing the sudden release of drugs through sustained-controlled release drugs, and has good mechanical strength and biocompatibility, which can well meet the repair and regeneration of bone tissue defects.
[0122] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A polycaprolactone stent, characterized in that: It comprises a polycaprolactone stent body, and a bonding layer and a drug-loaded layer which sequentially wrap the polycaprolactone stent body; The drug-loaded layer comprises drugs and zeolite imidazolate skeleton material; the drugs are encapsulated in the zeolite imidazolate skeleton material.
2. The polycaprolactone stent according to claim 1, characterized in that: The polycaprolactone stent body is a 3D printed stent.
3. The polycaprolactone stent according to claim 1, characterized in that: The component of the adhesive layer includes polyvinyl pyrrolidone.
4. The polycaprolactone stent according to claim 1, characterized in that: The matrix material of the polycaprolactone stent body includes polycaprolactone, and the molecular weight of the polycaprolactone is 27,000-65,000 Daltons.
5. The polycaprolactone stent according to claim 1, characterized in that: The drug includes at least one of bone morphogenetic protein-2, bone morphogenetic protein-7, vascular endothelial cell factor, platelet-derived factor, curcumin, melatonin, alendronate sodium, naringin, resveratrol, dexamethasone, and gentamicin sulfate.
6. The method for preparing the polycaprolactone stent according to any one of claims 1 to 5, characterized in that: The following steps are involved: The polycaprolactone stent body is placed in a solution containing a binder, stirred, and reacted; the product after the reaction is mixed with a drug and a 2-methylimidazole aqueous solution, and then a zinc nitrate aqueous solution is added and reacted to obtain the polycaprolactone stent.
7. The preparation method according to claim 6, characterized in that: The solution is an ethanol-water solution, the mass volume ratio of the binder to the ethanol-water solution is (0.55-1.65) g:10 mL, and the volume fraction of ethanol in the ethanol-water solution is 45-85%; and / or, the molecular weight of the binder is 10,000-58,000 Daltons; and / or, the mass volume ratio of the polycaprolactone stent body and the solution containing the binder is (1.8-11) mg:1 mL; and / or, the stirring speed is 180-550 rpm, and the stirring time is 0.9-4.5 h.
8. The preparation method according to claim 6, characterized in that: The concentration of 2-methylimidazole in the 2-methylimidazole aqueous solution is 22-65 mg / mL; and / or, the concentration of the drug in the 2-methylimidazole aqueous solution is 18-11000 μg / mL; and / or, the concentration of zinc nitrate in the zinc nitrate aqueous solution is 2.7-20 mg / mL; and / or, the volume ratio of the 2-methylimidazole aqueous solution to the zinc nitrate aqueous solution is (2.7-10):
1.
9. The preparation method according to claim 6, characterized in that: The method for preparing the polycaprolactone stent body comprises the following steps: Put polycaprolactone into a printing barrel, match a needle, and print to obtain the polycaprolactone stent body.
10. Use of the polycaprolactone scaffold according to any one of claims 1 to 5 in preparing products for repairing and regenerating bone tissue defects.